Bioecology and Uses of Desert Truffles (Pezizales) in the Middle East - OWAID, Mustafa Nadhim (Walailak Journal of Science and Technology (WJST), 2017)
Desert truffles grow naturally after rainfall during the season of Al-Wasm in arid and semi-arid districts of Saudi Arabia, Iraq, Kuwait, Qatar, Bahrain, United Arab Emirates, Syria, Jordan, Palestine, Lebanon, Egypt, Iran, Turkey, Tunisia, Algeria, Libya, and Morocco. Al-Wasm provides rainfall of more than 200 ml in September to October in the Arabian Peninsula, and is important for the early growth and appearance of desert truffles. The amount of truffles increases depending on the amount of rainfall, as in other countries. Two genera of desert truffles, Terfezia sp. and Tirmania sp., are the most abundant in the Middle East. Desert truffles have nutritional value due to their proteins, carbohydrates, fats, fibers, and low energy. Also, they have immune-modulating, hepatoprotective, antidepressant, antibacterial, antifungal, antiviral, antioxidant, and antiradical properties due to their content of phenol, carotenoid, anthocyanin, ascorbic acid, flavonoid, tannin, glycoside, ergosterol, etc. Hence, the introduction of desert truffles in the pharmacological field is important, especially in the treating of eye infections and cancer. Finally, the habitats of the truffles and the host-plants need protection as nature reserves.